2020
DOI: 10.4314/ijbcs.v14i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing biomolecules present in four proposed soft aqueous extractions of <i>Ageratum conyzoides</i> Linn

Abstract: Biochemically wound healing process is promoted by active agents which compose aqueous and alcohol herbal extracts and those components act synergistically. We propose in this study four methods of soft aqueous extraction (A, B, C, D) of Ageratum conyzoides Linn. leaves, a well-known west african plant for its wound healing properties. Our main objective was to know which of the extraction methods would allow us to obtain specifically tannins and flavonoids. We also investigated which types of flavonoids extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…TLC profiling for phenols detection showed that after the TLC plates were dipped in FeCl3 reagent and heated at 110 o C indicated a positive results because a grey to black colour was formed (Figure 2d) [19]. The TLC profiling for terpenoids detection gave the results after the TLC plates were sprayed with Vanillin-H2SO4 reagent and heated at 110 o C. The formation of blue to purple or brown color indicates a positive result (Figure 2e) [22]. In the terpenoid and phenol detection, the result showed that several crude extracts contained spots of the same Rf value.…”
Section: Resultsmentioning
confidence: 98%
“…TLC profiling for phenols detection showed that after the TLC plates were dipped in FeCl3 reagent and heated at 110 o C indicated a positive results because a grey to black colour was formed (Figure 2d) [19]. The TLC profiling for terpenoids detection gave the results after the TLC plates were sprayed with Vanillin-H2SO4 reagent and heated at 110 o C. The formation of blue to purple or brown color indicates a positive result (Figure 2e) [22]. In the terpenoid and phenol detection, the result showed that several crude extracts contained spots of the same Rf value.…”
Section: Resultsmentioning
confidence: 98%
“…Research works conducted in our laboratory on Ageratum conyzoides Linn. plant extract, demonstrated this extract contains flavonoids which are serine proteases inhibitors (Akpalo et al, 2020a).…”
Section: Discussionmentioning
confidence: 93%
“…Fibrin soft gels are formed subsequent to the thrombin hydrolysis of the fibrinogen molecules and fibrin polymerization. In our mind, phenomenon occurring, is certainly syneresis due first, to thrombin inhibition by plant extract substances previously demonstrated (Akpalo et al, 2020a); secondly, osmotic pressure leading to exudate of incorporated extract mixing with gel liquid phase and its molecules (ions, not attached fibrinogen and fibrin molecules,…). The stirring has pronounced this phenomenon.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TLC analysis using vanillin-sulfuric acid reagent performed the positive result of terpenoids for all extracts of G. verrucosa (F, A, 3D, 6D and 9D) which indicated by the presence of purple spot on TLC plate. Akpalo et al (2020) express that purple spot detected on TLC plate was expected as terpenoids.…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%